Integration of mRNA and miRNA analysis reveals the differentially regulatory network in two different Camellia oleifera cultivars under drought stress - He, Zhilong; Liu, Caixia; Zhang, Zhen; Wang, Rui; Chen, Yongzhong (Frontiers in Plant Science, 2022)
Camellia oleifera Abel. (C. oleifera) is an edible oil tree species that provide an important guarantee for targeted poverty alleviation strategy in China. Severe difficulties in irrigation leading to drought stress have become a major obstacle to the development of the C. oleifera planting industry. Breeding of drought-tolerant cultivars is the main idea for solving the problem of water shortage stress in C. oleifera cultivation. The photosynthetic physiology traits of C. oleifera cultivars ‘Xianglin No.1’ and ‘Hengdong No.2’ were affected by drought stress to different degrees, which demonstrated that the two cultivars suffered different degrees of damage. In the present study, we applied mRNA-seq and miRNA-seq to analyze the difference in molecular responses between drought stress and control, drought-tolerant and -sensitive cultivars, at mRNA and miRNA levels. The differentially expressed genes (DEGs) involved in photosynthesis-related, porphyrin, and chlorophyll metabolism, circadian rhythm system, and plant hormone signal transduction pathways were identified that might be candidates for drought stress tolerance genes. Subsequently, the miRNA-mRNA regulatory networks connected the differentially expressed miRNAs (DEMs) to their predicted target genes were established. miR398 and miR408-3p in C. oleifera showed that associated with the response to drought stress by negatively regulating genes encoding Downy Mildew Resistance 6 (DMR6) and Enhanced Disease Resistance 2 (EDR2), respectively, which might further improve drought tolerance via crosstalk between different stress-responsive pathways. The quantitation results of miRNA and mRNA were validated by quantitative real-time PCR (qRT-PCR). In summary, the integrated mRNA-seq and miRNA-seq analysis deepen our understanding of the regulatory network response to drought stress and variety-specific responses improving drought tolerance in C. oleifera.